Two “faces” of e-sports players: the relationship between facial width-to-height ratio and aggressive behavior in the virtual world - Xu, Zhengda; Li, Xiaohan; Lin, Song (Frontiers in Psychology, 2025)
IntroductionThe growing literature has emphasized the role of facial structures in affecting human behavioral tendencies, particularly the debate on whether a person’s facial width-to-height ratio (fWHR) influences their aggressive behavior. The development of the digital economy and e-sports—where players use virtual characters rather than engaging in physical fighting—provides a new research context. We aimed to explore the role of the fWHR of players, and the similarity to their virtual characters, in predicting aggressive behavior.MethodsWe utilized archival data from 954 professional League of Legend (LoL) players covering the period from 2017 to 2022. We analyzed the association between players’ fWHR and in-game indicators of aggressive behavior. We also assessed the effect of facial similarity between the player and their virtual character.ResultsWe present evidence that e-sports players’ fWHR is not significantly associated with their aggressive behavior in the virtual world. However, we found that players performed more aggressively when their real face was more similar to their virtual character’s face.DiscussionOur studies extend the boundary of fWHR and aggressive behavior research in the digital era.